2018
DOI: 10.1021/acs.orglett.8b00725
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Aza-Wacker Annulation: Tuning Mechanism by the Activation Mode of Amide and Enantioselective Syntheses of Melinonine-E and Strychnoxanthine

Abstract: An unprecedented N-substituent of the amide was found to be crucial for the successful annulation to establish 2-azabicyclo[3.3.1]nonane and other ring skeletons in good yield. The novel catalytic aza-Wacker annulation methodology was further illustrated in the concise syntheses and the absolute configuration determinations of melinonine-E and strychnoxanthine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Subjection of 16 to 17 and triflic anhydride (37, 38) and then NaBH 4 in MeOH delivered 1.05 grams of the anti-cancer agent (92% yield) as a single diastereomer. The stereochemical identity of synthetic (+)-tangutorine was confirmed by x-ray crystallography (formerly only that of racemic material was reported, despite the absolute stereochemical identity being known).…”
Section: Application To Natural Product Synthesismentioning
confidence: 99%
“…Subjection of 16 to 17 and triflic anhydride (37, 38) and then NaBH 4 in MeOH delivered 1.05 grams of the anti-cancer agent (92% yield) as a single diastereomer. The stereochemical identity of synthetic (+)-tangutorine was confirmed by x-ray crystallography (formerly only that of racemic material was reported, despite the absolute stereochemical identity being known).…”
Section: Application To Natural Product Synthesismentioning
confidence: 99%
“…30). 36,37 Cyclization precursor 8 was constructed from chiral lactone 7 in 2 steps; this lactone had previously been synthesized by Hong and co-workers as a key intermediate in the construction of other alkaloid natural products. 38 Interestingly, the N-substituent had a marked effect on the success of the aza-Wacker cyclization.…”
Section: Enantioselective Syntheses Of (à)-Melinonine-e and (+)-Strycmentioning
confidence: 99%
“…Hong and co-workers reported an eleganta za-Wacker annulation to access 2-azabicyclo[3.3.1]nonane and otherr ing systems( Scheme 8). [30] Remarkably,t he aza-Wacker reaction was successfully applied to thee nantioselective syntheses of two morphan core-embedded alkaloids, melinonine-E and strychnoxanthine.T he deuteriuml abeling experiments revealed that the activation modeo ft he amide for the amidopalladation process were able to be tuned by the N-substituent on the amide functionality. Nucleophilic addition of the N-Ts amide to the olefin proceeded through the direction anti to the palladium coordination and as ubsequent b-D cis-elimination led to the cyclizedp roduct 42 (X = Hb) as the major product (92 %), whilet he deuterated 42 (X = D) was obtained in only 8% yield.…”
Section: Miscellaneousmentioning
confidence: 99%